An Unusual Manifestation of Blastic Plasmacytoid Dendritic Cell Neoplasm as a Testicular Tumor - Daniel M. Pak; Maria S. Tretiakova (Hindawi Limited, 2019)
Blastic plasmacytoid dendritic cell neoplasm (BPDCN) is a clinically aggressive hematologic malignancy arising from precursors of plasmacytoid dendritic cells that represent less than 1% of hematological malignancies. BPDCN initially presents with cutaneous involvement and a characteristic immunophenotype of CD4, CD56, and CD123 co-expression. Upon disease progression, BPDCN shows a strong predilection for bone marrow, peripheral blood, and lymph nodes, whereas manifestations in visceral organs are rare. Significant heterogeneity in clinical presentation and immunophenotypic profile makes BPDCN challenging to diagnose without an integrated approach based on patient history, clinical features, tumor pathology, and comprehensive immunohistochemical studies. Herein we report the first case of relapsed BPDCN manifesting as a unilateral testicular tumor.